Neuronal Pentraxin 2 Binds PNNs and Enhances PNN Formation. (20th October 2019) - Van't Spijker, Heleen M.; Rowlands, Dáire; Rossier, Jean; Haenzi, Barbara; Fawcett, James W.; Kwok, Jessica C. F.
Abstract : The perineuronal net (PNN) is a mesh-like proteoglycan structure on the neuronal surface which is involved in regulating plasticity. The PNN regulates plasticity via multiple pathways, one of which is direct regulation of synapses through the control of AMPA receptor mobility. Since neuronal pentraxin 2 (Nptx2) is a known regulator of AMPA receptor mobility and Nptx2 can be removed from the neuronal surface by PNN removal, we investigated whether Nptx2 has a function in the PNN. We found that Nptx2 binds to the glycosaminoglycans hyaluronan and chondroitin sulphate E in the PNN. Furthermore, in primary cortical neuron cultures, the addition of NPTX2 to the culture medium enhances PNN formation during PNN development. These findings suggest Nptx2 as a novel PNN binding protein with a role in the mechanism of PNN formation.